A family of Vlasov–Maxwell equilibrium distribution functions describing a transition from the Harris sheet to the force-free Harris sheet. (June 2020) - Neukirch, T.; Wilson, F.; Allanson, O.
Abstract : We discuss a family of Vlasov–Maxwell equilibrium distribution functions for current sheet equilibria that are intermediate cases between the Harris sheet and the force-free (or modified) Harris sheet. These equilibrium distribution functions have potential applications to space and astrophysical plasmas. The existence of these distribution functions had been briefly discussed by Harrison & Neukirch ( Phys. Rev. Lett., vol. 102, (2009 a ), 135003), but here it is shown that their approach runs into problems in the limit where the guide field goes to zero. The nature of this problem will be discussed and an alternative approach will be suggested that avoids the problem. This is achieved by considering a slight variation of the magnetic field profile, which allows a smooth transition between the Harris and force-free Harris sheet cases.